Endocrine Complications in Children and Adolescents With Non-Central Nervous System Solid Tumors - Lee, Yena; Shin, Juhee; Choi, Yunha; Kim, Hyery; Koh, Kyung-Nam; Im, Ho Joon; Yoo, Han-Wook; Choi, Jin-Ho (Frontiers in Endocrinology, 2021)
Background: Due to remarkable progress in cancer treatment, endocrine complications are now the major medical issues facing childhood cancer survivors. Although non-central nervous system solid tumors (NCSTs) account for approximately 40% of all pediatric cancers, there have been few studies on endocrine complications associated with NCSTs. This study investigated endocrinopathies following the treatment of pediatric NCSTs. Design and setting: Retrospective study in a single academic center. Methods: This study analyzed 253 survivors of childhood NCSTs who were diagnosed between January of 2000 and December of 2018. The medical charts were reviewed regarding the frequency of endocrinopathies and treatment modalities. The hazard ratios were assessed by multivariable Cox regression analysis. The final height-SDS were analyzed by multivariable linear regression analysis. Results: There were 76 patients (30%) that developed at least one endocrine complication. Forty-four patients (17.4%) experienced endocrine complications within five years of their cancer diagnosis. The most common endocrine complication was growth failure (n = 35), followed by obesity (n = 18), and primary gonadal failure (n = 16). High cumulative doses of alkylating agents increased the risk of developing at least one endocrine complication. Hematopoietic stem cell transplantation was an important risk factor for primary gonadal failure. Conclusions: This study described the comprehensive endocrine outcomes, including growth failure, obesity, primary gonadal failure, primary hypothyroidism, dyslipidemia, and osteoporosis, following the treatment of childhood NCSTs. As endocrinopathies occurred within five years of primary tumor diagnosis, surveillance for endocrine dysfunction is required for early intervention and management.